QM/MM simulations of electronic transport properties for DNA sensing devices based on graphene - Martins, Ernane de Freitas (2018)
Nanotechnology is an important and very active area of research contributing to many different fields. The development of new devices applied to personalized medicine is one of its applications. When we desire to develop new devices many effort are done, including experimental and theoretical investigations. The theoretical/computational physics can enormously contribute to this area, since the simulations can reveal the working mechanism in these systems being possible to understand and propose new devices with improved performance. We present an extensive theoretical investigation of the electronic transport properties of graphene-based devices for DNA sensing. We have used a hybrid methodology which combines quantum mechanics and molecular mechanics, the so called QM/MM method, coupled to electronic transport calculations using non-equilibrium Green’s functions. First, we studied graphene in solution in order to understand the effects of polarization on the electronic and transport properties under different salt concentrations. We also stud- ied graphene with Stone-Wales defect in pure water. For these systems we tested a simple polarization model based on rigid rods. Our analysis were also done over different QM/MM partitions including explicit water molecules in the quantum part. Our results showed that the inclusion of the solvent in the electronic transport calculations for graphene decreases the total transmission, showing the important role played by the water. Our results also showed that the electronic transport properties of graphene do not suffer significant changes as we increase the salt concentration in the solution. The inclusion of polarization effects in graphene, despite changing the structuring of water molecules that make up the first solvation shell of graphene, do not significantly affect the electronic transport through graphene. We then studied DNA sequencing devices. First we focused on sequencing using a nanopore between topological line defects in graphene. Our results showed that sequencing DNA with high selectivity and sensitivity using these devices appears possible. We also address nanogap in graphene. For this we looked at the effects of water on electronic transport by using different setups for the QM/MM partition. We showed that the inclusion of water molecules in the quantum part increases the electronic transmission in several orders of magnitude, also showing the fundamental role played by water in tunneling devices. The electronic transport simulations showed that the proposed device has the potential to be used in DNA sequencing, presenting high selectivity and sensitivity. We propose an graphene-based biochip for sequence-specific detection of DNA strands. The main idea of this sort of device is to detect hybridization of single-stranded DNA, forming double-stranded DNA. We showed that the vertical DNA adsorption, either through an anchor molecule (pyrene) or using the nucleotide itself as anchor, do not present good results for detection, since the signals for the single and double strands are quite similar. For the case of horizontal DNA adsorption on graphene our results indicated that the two signals can be distinguishable, showing promising potential for sensitivity and selectivity.